2009
DOI: 10.1080/00016480801998838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Japanese herbal medicine, Juzen-taiho-to, in otitis-prone children – a preliminary study

Abstract: Medication compliance rate was 87.5%, and administration of JTT led to remission in 95.2% patients. No apparent side effects were observed. The frequency of AOM decreased significantly (Wilcoxon signed rank test, p=0.000) with JTT. The duration of fever (p=0.000) and administration of antibiotics (p=0.001), as well as the number of hospital visits (p=0.001) and emergent hospital visits (p=0.000) showed significant decreases after JTT administration. After the end of the JTT period, 14 of 21 (66.7%) patients st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…JTT has been used as an adjunctive therapy for advanced breast cancer patients [16]. A recent report indicated that JTT aided in preventing the recurrence of otitis [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JTT has been used as an adjunctive therapy for advanced breast cancer patients [16]. A recent report indicated that JTT aided in preventing the recurrence of otitis [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Although no severe side effects have been reported for JTT [14, 17, 21]. In the early stage, many patients dropped out of JTT group in comparison with control group.…”
Section: Discussionmentioning
confidence: 99%
“…15 JTT is used clinically in East Asia to strengthen the immune functions of patients with various diseases, including cancer, 16,17 hepatitis C, 18 and otitis. 19 The formulation is a mixture of ten different herbs (see Table S1 in Supplementary data). The active factors in JTT have not yet been clarified due to its chemical complexity.…”
mentioning
confidence: 99%
“…AOM is defined as the presence of middle-ear effusion and the rapid onset of one or more signs or symptoms of middle-ear inflammation, such as an earache, ear rubbing, a bulging eardrum or fever 6. AOM can progress to recurrent AOM, otitis media with effusion or conditions that are more serious, such as mastoiditis, meningitis, cerebritis and sigmoid sinus thrombosis 7 8…”
Section: Introductionmentioning
confidence: 99%
“…Also, many types of herbal medicines have anti-inflammatory and antibacterial effects, such as increasing the phagocytosis for clearing up an infection 8 19–21. However, it is unclear how they work, in spite of observed immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%